Determination of fifteen water and fat-soluble UV filters in cosmetics by pressurized liquid extraction followed by liquid chromatography tandem mass spectrometry. Issue 37 (7th September 2016) - Vila, Marlene; Facorro, Rocio; Lamas, J. Pablo; Garcia-Jares, Carmen; Dagnac, Thierry; Llompart, Maria
Abstract : An analytical method based on pressurized liquid extraction followed by high performance liquid chromatography tandem mass spectrometry was developed for the simultaneous analysis of fifteen organic UV filters. Abstract : An analytical method based on pressurized liquid extraction (PLE) followed by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was developed for the simultaneous analysis of fifteen different organic UV filters, both water and fat soluble, in cosmetic products. The extractions were carried out in 10 mL extraction cells and the amount of sample employed was only 100 mg. Several factors affecting the PLE procedure such as the extraction solvent and the dispersive agent used to fill the PLE cell were studied. The use of smaller cells (1 mL) and with Teflon as an inner cell coating was also evaluated. Good linearity ( R 2 > 0.991), quantitative recoveries (82–101%), and satisfactory precision (RSD < 12%) were obtained under the optimal conditions. LOQ values <0.1 μg g −1 were achieved. The proposed methodology was applied to the analysis of daily personal care products, specific sunscreen products, and cosmetics, such as moisturizing creams, facial creams, anti-wrinkle creams, body milks, hair care products, nail polish, make-up, color lipsticks, lip glosses, protector lipsticks, sun milks, sun sticks, facial sun creams, and sun lotions. For quantification purposes, an external calibration method was implemented since significant matrix effects were not observed. Nine out of the target compounds were found, frequently in combinations of 2–3 compounds, at concentrations ranging from 0.044 to 9.6%. In all cases, these compounds were correctly included in the product label.